Strategi Adaptasi Pembelajaran Tatap Muka Terbatas pada Masa COVID-19 di SMA Negeri 5 Kupang - Safrida Un (PENSOS : Jurnal Penelitian dan Pengabdian Pendidikan Sosiologi, 2023)
The purpose of this study was to determine the adaptation strategy of limited face-to-face learning at SMA Negeri 5 Kupang and the factors that hindered the limited face-to-face learning strategy. This study used qualitative methods. Data collection techniques were carried out through observation, interviews, and documentation. The data analysis technique used interactive analysis which consists of stages of data collection, data reduction, data presentation, and conclusion drawing. The results of this study indicate that the face-to-face learning adaptation strategy that was limited to the COVID-19 period at SMA Negeri 5 Kupang had been carried out quite well. It was proven (1) choosing the right learning method (the teacher was obsessed with using the appropriate method), (2) designing media learning (planning the use of learning media and evaluating learning), (3) making learning preparations (preparing teaching materials and materials, determining learning objectives, and preparing learning implementation plans). While the factors that hinder the limited face-to-face learning adaptation strategy were (1) the delivery of the material was not optimal. It was related to the limited duration of learning which was only three hours on average, (2) student learning motivation was decreasing, students learn and depend on assignments belonging to their friends, and less effort to study the material, and (3) the situation and conditions during the COVID-19 made communication and collaboration with students less extensive and limited in time where face-to-face meetings were limited under strict supervision.